Bone Vascularization in Normal and Disease Conditions - Carulli, Christian; Innocenti, Massimo; Brandi, Maria Luisa (Frontiers in Endocrinology, 2013)
Bone vasculature is essential for many processes, such as skeletal development and growth, bone modeling and remodeling, and healing processes. Endothelium is an integral part of bone tissue, expressing a physiological paracrine function via growth factors and chemokines release, and interacting with several cellular lines. Alterations of the complex biochemical interactions between vasculature and bone cells may lead to various clinical manifestations. Two different types of pathologies result: a defect or an excess of bone vasculature or endothelium metabolism. Starting from the molecular basis of the interactions between endothelial and bone cells, the Authors present an overview of the recent acquisitions in the physiopathology of the most important clinical patterns, and the modern therapeutic strategies for their treatments.